Authorship Pattern & Research Collaboration of Bifurcation Research During 2016-2020: A Scientometric Analysis - Parida, Dillip Kumar; Nayak, Satyajit (International Journal of Knowledge Content Development & Technology, 2023)
This study depicts a Scientometric technique of Bifurcation Research output in India for around five years during 2016-2020. It is an active field of analysis in which the bulk of investigation is being done. Scopus is an advanced research platform, assisting in finding, probing and yielding information in the sciences, social sciences, arts, and humanities. The contemporary study discusses the “Bifurcation” as reflected in SCOPUS for 2016-2020. This study examines the highly prolific authors, document type etc. The study exhibited that 2017 shown maximum research papers 1700 (20.44%), the lowermost maturity rate was deciphered in 2018 (19.65%), the standard value of the period of collaboration is 0.18. The time series examines for single-authored, multi-authored, and collaborative papers are 137.8, 1564 and 1701.8 respectively.